La agricultura en las negociaciones sobre cambio climático - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
As the specialized agency of the Inter- American System for agriculture, IICA collaborates with the institutions of its member countries, especially the ministries of agriculture, in the design of public policies, the elaboration and implementation of sectoral